Linguagem e comunicação em Heidegger - CASTRO, Fábio Fonseca de (Pontifícia Universidade Católica de São Paulo, 2022)
This article discusses the ontological dimension in the Heideggerian category of “talking,” based on which we seek to make an interpretation of communication as a fundamentally intersubjective phenomenon. To this end, we use Heidegger’s Being and Time. We begin by explaining Heidegger’s concept of language, which he discusses in the above cited book, to gain an understanding of this philosopher’s concept of communication. We seek to demonstrate that talking is equivalent to giving ordinary meaning to something: not the encounter, the revelation, of the meaning itself of something, in its so-called ontical dimension, but the meaning present in intersubjectivity, in the shared world, and in the resources of understanding that the individual uses in his interactions with others. Based on this rationale, we seek to demonstrate that philosophical reflections about language and communication should be rooted in the ontology of being-with-others in order to go beyond the bounds of the individual’s metaphysics and of subjectivity in order to gain a deeper understanding of the phenomenon of intersubjectivity.